Statutory clauses on the post mortem transfer of shares and participations and Succession Law - Carrillo Pozo, Luis F. (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The exclusion by the SR of matters regulated by corporate rules is clear in assigning to the lex societatis the modalities for the transfer of shares and participations, but it leaves open the question of how statutory provisions restricting or conditioning access to membership are related to a lex successionis that provides for a compulsory share of the relict estate to a certain group of persons. The answer is based on the imperativity – and therefore prevalence/intangibility– of succession rules.
Keywords: Succession Regulation; company statutes; compulsory shares